Malaysia as an emerging middle power : an evaluation of its South-South Cooperation policies, 1981-2003 - Ramasamy, Selvaraj (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This thesis analyses the foreign policy behavioral patterns of Malaysia from 1981 to 2003 using the concept of an emerging middle power. In so doing, this study also helps to clarify a significant period (1981-2003) of Malaysia's foreign policy using the framework of the emerging middle power. Hence, by critically analysing the strategies under the South-South Cooperation, it provides another dimension of explanation to the country's foreign policies. The study attempted to investigate three critical strategies associated with the South-South Cooperation policies, which were: the Malaysian Technical Cooperation Programme (MTCP), the South Investment, Trade and Technology Data Exchange Centre (SITTDEC) and Bilateral Payment Arrangements (BPA) arrangements and as the Chair of Commission on Sustainable Development (1992-1993). The study is evaluative in nature. This study comprises library research and field research. Data collected were on information regarding policies, strategies applied and the actual practices in the implementation of the Malaysian Technical Cooperation Programme (MTCP), fostering economic relations with countries of the South in the Group of 15 (G-15) using the South Investment, Trade and Technology Data Exchange Centre (SITTDEC) and Bilateral Payment Arrangements (BPA) and the role of Malaysia in voicing the countries of South's interest on environment and sustainable development issues in the Rio Earth Summit (1992) and as the Chair of Commission on Sustainable Development (1992-1993).These data have been analysed based on the behavioural patterns of an emerging middle power, corresponding with foreign policy of Malaysia from 1981 to 2003. The findings from this study suggest that, it is now possible to state that Malaysia can be identified as an emerging middle power not only because of its features as explained by Eduard Jordaan's (2003) theoretical framework of emerging middle power, but also because it fulfills the foreign policy behavioural patterns of an emerging middle power. The three behavioural patterns of the concept of an emerging middle power that have been pursued in this study are preference to pursue multilateralism, playing an active role in reforming global agenda and act as a good international citizen. When applying these behavioural patterns to analyse strategies of South-South Cooperation, it has fulfilled the foreign policy behavioural patterns of an emerging middle power. The study also detects Malaysia's active role in international fora during the period of 1981–2003, had increased its international prestige. Further, the study found out that the economic relations have changed the state of affairs of the countries of the South. South-South Cooperation policies have also created strained relationship between the countries of the South and countries of the North, in particular when Malaysia was the most vocal opponent to any suggestion that their natural resources should be "internationalized" during the Earth Summit and urged countries of the North to build consensus on the sustainable development forestry with the countries of the South. Finally, this study also provides recommendations to the Malaysian government to further continue to play its role as an emerging middle power by representing the countries of the South in speaking about issues confronting these countries with practical solutions as Malaysia continues to render its modest technical assistance under the auspices of MTCP to further strengthen the human capital of countries of South.